OP0012 TNF INHIBITORS ARE ASSOCIATED WITH A REDUCED RISK OF VENOUS THROMBOEMBOLISM COMPARED TO CSDMARDS IN RA PATIENTS. (2nd June 2020) - Schaefer, M.; Schneider, M.; Graessler, A.; Ochs, W.; Zink, A.; Strangfeld, A.
Abstract : Background: While the short-term use of bDMARDs up to 180 days has been associated with an increased risk of venous thromboembolism (VTE) compared to csDMARDs in patients with rheumatoid arthritis (RA), the long term use of more than 730 days has been associated with a decreased risk based on claims data [1]. Among patients with inflammatory bowel disease, observational data indicated that TNF inhibitors may have a protective effect regarding the VTE risk [2]. Objectives: To assess the effects of TNF inhibitors and newer bDMARDs (including abatacept, rituximab, sarilumab, and tocilizumab) on the VTE risk based on observational data from RA patients. Methods: The German register RABBIT is a prospective longitudinally followed cohort of RA patients enrolled with a new start of a DMARD after at least one csDMARD failure. This analysis comprises patients who were enrolled with start of a bDMARD between 01/2009 and 04/2019 and had at least one follow-up. Cox regression models were used to calculate hazard ratios (HRs) for VTEs, for csDMARDs, TNF inhibitors and other bDMARDs. Propensity score weighting was used to adjust for confounding by indication. Results: Patients receiving TNF inhibitors or other bDMARDs on average had higher CRP levels and a higher prevalence of cardiovascular diseases at baseline than patients receiving csDMARDs. They also received more often glucocorticoids (Table 1 ). The HR of patients receiving TNF inhibitors for a serious VTE event was 0.53 (95% CI: 0.33 – 0.86) compared to csDMARDs, while the HR for patients receiving other bDMARDs was 0.66 (95% CI: 0.40 – 1.09). A CRP level of more than 5 mg/L (HR 2.09, 95% CI: 1.39 – 3.14) and an age above 65 years (HR 2.96, 95% CI: 1.94 – 4.52) increased the risk for a serious VTE event. Better physical function was associated with a decreased risk for VTEs (Table 2 ). Conclusion: Treatment with TNF inhibitors (compared to csDMARDs) and better physical function significantly reduced the risk of serious VTE events, while age above 65 years and high CRP levels increased this risk. References: [1]Kim S. C. et al. Am. J. Med. 2015; 128(5): 539.e7–539.e17. [2]Desaj R.J. et al. CMAJ 2017; 189:E1438-47. Acknowledgments: RABBIT is supported by a joint, unconditional grant from AbbVie, Amgen, BMS, Fresenius-Kabi, Hexal, Lilly, MSD, Mylan, Pfizer, Roche, Samsung Bioepis, Sanofi-Aventis, and UCB. Disclosure of Interests: Martin Schaefer: None declared, Matthias Schneider Grant/research support from: GSK, UCB, Abbvie, Consultant of: Abbvie, Alexion, Astra Zeneca, BMS, Boehringer Ingelheim, Gilead, Lilly, Sanofi, UCB, Speakers bureau: Abbvie, Astra Zeneca, BMS, Chugai, GSK, Lilly, Pfizer, Sanofi, Anett Graessler: None declared, Wolfgang Ochs: None declared, Angela Zink Speakers bureau: AbbVie, Amgen, BMS, Gilead, Hexal, Janssen, Lilly, MSD, Pfizer, Roche, Sanofi Aventis, UCB, Anja Strangfeld Speakers bureau: AbbVie, BMS, Pfizer, Roche, Sanofi-Aventis